2002
DOI: 10.1007/s00234-001-0753-z
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution MRI study of linear growth of the human fetal skull base

Abstract: The skull base, otherwise referred to as the basicranium or cranial base, plays a key role in the process of skull development, providing both support for the brain and an architectural component of the craniofacial complex. Consequently, the fetal skull base has been the focus of numerous studies employing various methods, including sectioning, plain radiography and CT. This paper investigates high-resolution (hr) MRI as an alternative method for looking at and quantifying the fetal skull base. The evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…Their method may have averaged-out the subtle but significant (slope=0.28) intervening changes of cranial base angle seen in the present investigation. Lastly, all the aforementioned studies employed radiographic techniques and so radio-translucent cartilaginous parts of the fetal basicranium may not have been properly imaged (see Jeffery, 2002b). With these technicalities in mind, it would appear the reported angulations are not comparable to those outlined in the present study.…”
Section: Growth Trendsmentioning
confidence: 70%
“…Their method may have averaged-out the subtle but significant (slope=0.28) intervening changes of cranial base angle seen in the present investigation. Lastly, all the aforementioned studies employed radiographic techniques and so radio-translucent cartilaginous parts of the fetal basicranium may not have been properly imaged (see Jeffery, 2002b). With these technicalities in mind, it would appear the reported angulations are not comparable to those outlined in the present study.…”
Section: Growth Trendsmentioning
confidence: 70%
“…All measurements were computed from landmark coordinates taken from midline hrMR images or parasagittal images close to the midline with the ImageJ software package (Wayne Rasband) and Align3D plugin (Nick Parker). Previous studies have shown that this is a precise and accurate method for studying fetal morphology (Jeffery, 2002;Jeffery and Spoor, 2004). It should be remembered, however, that previous studies also indicate that head orientation influences laryngeal position (Magriples and Laitman, 1987).…”
Section: Measurementsmentioning
confidence: 90%
“…Consequently, the head region of each fetus was noninvasively scanned with high-resolution magnetic resonance imaging (hrMRI). This technique offers a number of advantageous over traditional methods such as sectioning or plain film radiography described in detail elsewhere (Jeffery, 2002). The major benefits include that hrMRI is noninvasive and can demonstrate soft as well as hard tissues, albeit indirectly by contrast against softer tissues (i.e., greater water or fat content).…”
Section: Sample and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the anterior cranial base has a more active and more prolonged growth process that lasts to a very late growth stage. 4,5 This feature is a prerequisite for coordinated craniofacial development and growth. The basicranium also differs from other portions of the endochondral skeleton; to a great extent, the development and growth of the basicranium are under the influence of the brain, and the final shape and size of the basicranium follow that of the brain.…”
Section: Introductionmentioning
confidence: 99%